Theory of laser-induced photoemission from a metal surface with nanoscale dielectric coating - Zhou, Yang; Zhang, Peng (Journal of applied physics, 2022)
This paper presents an analytical quantum model for photoemission from metal surfaces coated with an ultrathin dielectric, by solving the 1D time-dependent Schrödinger equation subject to an oscillating double-triangular potential barrier. The model is valid for an arbitrary combination of metal (of any work function and Fermi level), dielectric (of any thickness, relative permittivity, and electron affinity), laser field (strength and wavelength), and dc field. The effects of dielectric properties on photoemission are systematically investigated. It is found that a flat metal surface with dielectric coating can photoemit a larger current density than the uncoated case when the dielectric has smaller relative permittivity and larger electron affinity. Resonant peaks in the photoemission probability and emission current are observed as a function of dielectric thickness or electron affinity due to the quantum interference of electron waves inside the dielectric. Our model is compared with the effective single-barrier quantum model and modified Fowler–Nordheim equation, for both 1D flat cathodes and pyramid-shaped nanoemitters. While the three models show quantitatively good agreement in the optical field tunneling regime, the present model may be used to give a more accurate evaluation of photoemission from coated emitters in the multiphoton absorption regime.